Pengaruh disiplin dan pelatihan terhadap kinerja karyawan bagian penjualan PT. Coca Cola Amatil Indonesia Cabang Pekanbaru - Ameliyah, Usroh; Daulay, Iwan Nauli; ', Marzolina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The research was conducted at PT. Coca-Cola Amatil Indonesia The Branch Of Pekanbaru. This study aims to determine how Effect of Work Dicipline and Training either simultaneously or partially on Employee Performance Parts Sales in PT. Coca-Cola Amatil Indonesia Pekanbaru Branch The population in this study is a sales employee of PT. Coca-Cola Amatil Indonesia The Branch Of Pekanbaru totaling 52 people, with a total sample of 52 employees. methods of analysis used in this study is the method of multiple linear regression analysis. By using SPSS version 17. The result of study concluded that simultaneously both variable Discipline and Training influencend significantly toward Employee Performance. Partially, the results obtained were that the variable of Discipline influenced significantly toward the variable of Emlpoyee Performance and the variable of Training influencend significantly toward the variable of Emlpoyee Performance. This writer concluded that concluded that the variable of Discipline an Training simultaneously and partially influenced positively and significantly toward Empolyee Performance PT. Coca Cola Amatil Indonesia The Branch Of Pekanbaru.Keywords: Discipline, Training And Employee Performance